MANAJEMEN PEMBELAJARAN DI TAMAN KANAK-KANAK (STUDI KASUS DI TK DAHLIA NAGRAK) - Jimatul Arobbi; Mariana Panji Ramadan (Jurnal El-Audi, 2022)
This study aims to determine the management of learning in TK Dahlia Nagrak which implements an integrated education system between general education, religious education, and life skills education with a semi-private. This research uses a qualitative approach and is a case study. The research subjects were the principal and the teachers. Data was collected through observation, interviews, and documentation. checking the validity of the data by checking the source of the data obtained and the method of data acquisition so that the data is truly valid as a basis and material for giving meaning to the data which is a determining process in understanding the context of the research being studied. The results of the study indicate that the management of learning in DahliaNagrak Kindergarten is structured according to the vision and mission of the institution by carrying out management functions, including; planning, implementation, monitoring and assessment. Planning is carried out by strategic planning, preparation of learning plans starting from annual and semi-annual planning, weekly activity units and daily activity units. Organizing is done by coordinating tasks, opportunities, experiences and insights with open communication, holding regular meetings that discuss efforts to improve the achievement of learning objectives. The action of learning begins with welcoming children or shaking hands with the teacher, introduction (morning exercise and marching, praying), core activities, eating and resting, closing. Assessment is carried out by making portfolios, assessing work, evaluating performance, evaluating actions and observing daily to ensure students' absorption of the lessons given.